2014
DOI: 10.3103/s0891416814040120
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic identification of the bovine leukemia virus

Abstract: Phylogenetic analysis of the sequenced segments of the env gene locus of the BLV provirus and the PCR RFLP genotyping strategy proposed in our works that is consistent with phylogenetic classification of this pathogenic agent allowed the taxonomic identification of BLV isolates identified in cattle in Tatarstan (Russian Federation) as representatives of BLV genotypes 4, 7, and 8. Of the 100 isolates identified, 64 were attributed to BLV genotype 4; 28 BLV representatives belong to the cluster of genotype 7; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Analysis of BLV gp51 env gene sequences from different locations throughout the world revealed the presence of different genetic groups that correlated with geographic origin [ 12 , 21 ], and thus, the nucleotide and amino acid sequences composition of gp51 are useful genomic markers of BLV in studies of geographical distribution [ 9 ]. A phylogenetic study of BLV env gene has so far identified at least 10 genotypes in the world [ 5 , 7 , 8 , 14 , 16 , 19 ].…”
mentioning
confidence: 99%
“…Analysis of BLV gp51 env gene sequences from different locations throughout the world revealed the presence of different genetic groups that correlated with geographic origin [ 12 , 21 ], and thus, the nucleotide and amino acid sequences composition of gp51 are useful genomic markers of BLV in studies of geographical distribution [ 9 ]. A phylogenetic study of BLV env gene has so far identified at least 10 genotypes in the world [ 5 , 7 , 8 , 14 , 16 , 19 ].…”
mentioning
confidence: 99%
“…When looking at the geographical context of these genotypes, it is clear that their dispersal is specifically associated with the northern and southern part of the Asian continent. While in the northern part the genotypes G4, G7 and G8 were exclusively identified in countries like Mongolia, Russia and Kazakhstan [26,[45][46][47], in the…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of the last decade have identified 11 BLV genotypes, however, the features of genotype-associated pathogenesis have not been studied [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%